British rubber manufacturing : - Donnithorne, Audrey. (Gerald Duckworth, 1958)
Contents: An outline of the structure of the bristish rubber manufactoring industry, Developments in rubber compounding, Synthetic rubber, Tyres and tubes, Rubber footwear, Latex-General, Latex foam and other cellular rubbers, dipped goods,....